Formative Assessment Practices in Online Learning for Assessing the Junior High School Students’ Reading Comprehension - Putu Enik Kristiani; Ni Luh Putu Eka Sulistia Dewi; Ni Putu Era Marsakawati (Institut Agama Islam Negeri Palopo, 2022)
The development of students’ reading comprehension can be reached by implementing formative assessment during the reading instruction so that the teachers are able to monitor students’ reading comprehension progress and make a development. Due to the Covid-19 Pandemic, the teachers faced a new learning situation namely online learning. However, conducting formative assessment for assessing students’ reading comprehension has to be conducted constantly. Therefore, this study aimed to investigate the formative assessments practices by the teachers for assessing students’ reading comprehension in online learning, include the plan and its implementations. The implementations of FA were gained from teachers’ point of view. The study involved four junior high school English teachers at SMPN 7 Denpasar. The design of the study was qualitative study. The data were collected by using three methods namely document analysis, survey, and interview. The result of the study showed that there were several formative assessment methods that were planned and implemented by teachers. Those methods were categorized into self-assessment, peer-assessment, teacher-feedback, sharing an understanding of formative assessment goals, and varied assessment methods.